Beyond Immunuhistochemistry: Molecular Insights Into Round Cell Soft Tissue Tumors - Prashanth Kumar Madoori; Sujatha Tejavat (Perspectives In Medical Research)
Round cell soft tissue tumors (RCSTTs) are a diverse group of aggressive malignancies that share overlapping clinical, morphological, and immunohistochemical features, posing significant diagnostic challenges. Recent advances in molecular pathology have revolutionized the understanding and classification of these tumors by identifying tumor-specific genetic alterations. This review highlights the role of molecular insights in complementing histopathology and immunohistochemistry to achieve precise diagnosis, risk stratification, and therapeutic decision-making. Key subtypes, including Ewing sarcoma, CIC- and BCOR-rearranged sarcomas, alveolar rhabdomyosarcoma, desmoplastic small round cell tumor, and extraskeletal myxoid chondrosarcoma, are discussed with emphasis on their molecular signatures and clinical significance. The advent of techniques such as fluorescence in situ hybridization (FISH), reverse transcriptase-polymerase chain reaction (RT-PCR), and next-generation sequencing (NGS) has enabled detection of genetic fusions and aberrations critical for tumor identification and targeted therapies. Integration of molecular pathology with traditional diagnostic approaches is essential for improving diagnostic accuracy, prognostication, and therapeutic strategies, paving the way for personalized medicine in the management of RCSTTs. Full form of ABBREVIATIONS are provided at the end.